Relationship between ESL teachers’ reading habits and their English language proficiency / Sharmila Appa Rwoo - Sharmila , Appa Rwoo (2020)
This research is carried out with the purpose of gaining more in-depth information in regards to the reading habits of 210 ESL teachers in the district of Klang, Selangor and how these habits correspond to their English language proficiency. Using the convenience sampling method and quantitative instruments such as survey questionnaire and an English language proficiency test, this research aims to achieve four research objectives. First, it intends to study the types of reading materials read by ESL teachers in Malaysia. Secondly, it aims to calculate the rates of general and extensive reading among these teachers and thirdly, the problems faced by them which prevent them from partaking in leisure reading extensively. Finally, this research hopes to find the relationship between the reading habits of ESL teachers and their English language proficiency. This is done by calculating the Pearson‟s R value using SPSS software. As a result, it is found that ESL teachers in Malaysian read mostly light reading materials and tend to shun heavy materials. The researcher also discovered that the rates of general and extensive reading among Malaysian ESL teachers are high and average respectively. The third finding identifies teachers‟ heavy workload as the most pressing problem which hinders the teachers from reading for leisure. The final finding uncovers a moderate correlation (r = 0.677) between ESL teachers‟ reading habits and their English language proficiency. This researcher hopes that the findings of this research help in upcoming studies or programmes carried out to improve ESL teachers‟ language proficiency in the effort to develop and improve the standards and quality of English language teaching in Malaysia.